Sharecropper Finance: Using the Justice System as a Public Revenue Source. (2nd April 2016) - Blessett, Brandi; Box, Richard C.
Abstract : Fines and fees charged to lower-income people, mostly African Americans, have long been a mainstay of the revenue stream for the city of Ferguson, Missouri, and other local governments. One outcome of this practice is financial dependency that limits the life-choices of the affected population. This current policy issue shares characteristics with the much older technique of sharecropping, suggesting a long-term pattern of financial exploitation based on race. The authors use a critical race theory framework to examine the question of administrative ethics raised by this practice.